Detection of Environmental DNA from Tree Bark Associated with Rubbing Behavior of Dicerorhinus sumatrensis in Way Kambas National Park - Priyambodo; Zulkarnain, Danisworo; Rustiati, Elly Lestari; Kurniawati, Yeyen; Putri, Chicka Refina Rahma; Srihanto, Eko Agus; Saswiyanti, Enny; Arsan, Zulfi; Sukatmoko; Pratiwi, Dian Neli; Permatasari, Nindy (ORGANISMS: JOURNAL OF BIOSCIENCES, 2026)
The development of non-invasive methods is essential for monitoring critically endangered species such as the Dicerorhinus sumatrensis. This study aimed to evaluate the potential of tree bark associated with rubbing behavior as a source of environmental DNA (eDNA) for species detection in Way Kambas National Park. A total of 30 samples were collected from tree bark surfaces showing evidence of rubbing activity. DNA was extracted and analyzed using two approaches: simple electrophoresis and polymerase chain reaction (PCR)-based molecular methods. The results showed that the simple method failed to detect visible DNA bands, indicating low DNA concentration and degradation in environmental samples. In contrast, PCR amplification successfully detected DNA in 5 out of 30 samples, including hair-derived and epithelial residues associated with rubbing behavior.containing hair residues produced more reliable detection compared to those with only epithelial traces. These findings demonstrate that tree bark able to serve as a potential non-invasive source of eDNA, particularly when analyzed using sensitive molecular techniques. This approach provides an alternative method for detecting elusive species and contributes to the development of effective conservation strategies for the sumatran rhinoceros.